Resin composition and resin molded article made from the resin composition

JP7631805B2Active Publication Date: 2025-02-19TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020540825
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-24
Filing Date
2020-07-16
Publication Date
2025-02-19
Estimated Expiration
2040-07-16

Smart Images

  • Figure 0007631805000015
    Figure 0007631805000015
  • Figure 0007631805000016
    Figure 0007631805000016
  • Figure 0007631805000017
    Figure 0007631805000017
Patent Text Reader

Abstract

An objective of the present invention is to provide a resin composition that strikes a balance between the properties of a high level of fuel permeation resistance and fusibility with a fusion substrate (polyolefin resin), and also yields a resin molded article that is free of surface debonding and the like. In the resin composition, the respective proportions of (a) a polyolefin resin and (b) a polyamide resin are 70–30% by weight and 30–70% by weight, wherein the total of the polyolefin resin (a) and the polyamide resin (b) is 100% by weight. The surface of a resin molded article made of the resin composition, when measured using microscopic infrared spectroscopy, has a spectrum peak strength ratio of 3.0–5.0 as calculated according to formula (1).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a polyolefin resin and a polyamide resin, which has excellent fuel permeation resistance, and excellent weldability and moldability with the polyolefin resin.Furthermore, the present invention relates to a resin molded product made of the resin composition. [Background technology]

[0002] In recent years, in fields such as fuel tanks, there has been an increase in plastic products with permeation resistance for the purpose of preventing leakage of contents and mixing of outside air in order to ensure safety, storage stability, and further to prevent environmental pollution. In particular, in the case of automobile fuel tanks and their peripheral parts, a shift from metal products to plastic products has been actively considered from the viewpoints of light weight, ease of molding, freedom of design, ease of handling, etc.

[0003] Polyolefin resins such as polyethylene resin and polypropylene resin are the mainstream materials for plastic products for such applications, but since polyolefin resins alone do not have sufficient fuel permeation resistance, they are used in a form bonded to a molded article that exhibits permeation resistance. Such a bonded surface is likely to affect the physical properties of the resulting molded article.

[0004] As a method for improving these properties, a method has been proposed in which a polyolefin resin is alloyed with a thermoplastic resin other than a polyolefin resin to control the phase structure (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4032656 Summary of the Invention [Problem to be solved by the invention]

[0006] However, although the technology described in Patent Document 1 is excellent in permeation resistance and weldability, it is insufficient in terms of molding processability with respect to surface peeling of a resin molded product.

[0007] In recent years, there has also been a demand for materials that have excellent adhesion and weldability with polyolefin resins, as well as moldability, such as high yields of molded products, i.e., molded products free from defects in appearance such as surface peeling.

[0008] In view of the above problems of the prior art, the present invention aims to provide a polyamide resin composition which has both high fuel permeation resistance and weldability to a weldable material (polyolefin resin). Another object of the present invention is to provide a polyamide resin composition which has excellent moldability and which produces a resin molded product free from surface peeling. [Means for solving the problem]

[0009] The present invention mainly has the following configuration. [1] A resin composition in which the blending ratios of (a) polyolefin resin and (b) polyamide resin are 70 to 30% by weight and 30 to 70% by weight, respectively, relative to 100% by weight of the total of (a) polyolefin resin and (b) polyamide resin, and in which, when the surface of a resin molded product made of the resin composition is measured by microscopic infrared spectroscopy, the peak intensity ratio of the spectrum obtained based on the following formula (1) is 3.0 to 5.0.

[0010]

number

[0011] [2] The resin composition according to [1], wherein (a) the polyolefin resin comprises (a-1) a modified polyolefin resin and (a-2) an unmodified polyolefin resin. [3] The resin composition according to [2], wherein the acid value of the (a-1) modified polyolefin resin is 12 mgKOH / g to 35 mgKOH / g. [4] (a) The resin composition according to [1] or [2], characterized in that the polyolefin resin comprises a polyolefin resin modified with at least one compound selected from unsaturated carboxylic acids and derivatives thereof. [5] (a) The higher of the melting points of polyolefin resin and polyamide resin is Tp (℃), and the melt viscosity ratio at Tp + 20℃ defined by the following formula (2) is -1 The resin composition according to any one of [1] to [4], wherein the R is 0.35 to 0.64.

[0012]

number

[0013] [6] The resin composition according to any one of [1] to [5], characterized in that a dumbbell-shaped test piece conforming to JIS K7139 (2009) Type A1 and having a total length of 170 mm, a parallel part length of 80 mm, a parallel part width of 10 mm, and a thickness of 4 mm is prepared, and the test piece is immersed in water at 23°C for 24 hours to measure a change in weight, and the water absorption calculated by the following formula (3) is 0.26% to 0.50%.

[0014]

number

[0015] [7] (a) The resin composition according to any one of [1] to [6], characterized in that a molded article made of the polyolefin resin has a flexural modulus of 0.5 to 1.3 GPa. [8](b) The resin composition according to any one of [1] to [7], characterized in that a molded article made of the polyamide resin has a flexural modulus of 2.5 to 3.0 GPa. [9] The resin composition according to any one of [1] to [8], characterized in that the blending ratios of the (a-1) modified polyolefin resin and the (a-2) unmodified polyolefin resin are 1 to 46% by weight and 99 to 54% by weight, respectively, relative to 100% by weight of the total of the (a-1) modified polyolefin resin and the (a-2) unmodified polyolefin resin.

[10] Any one of [1] to [9] above. A resin molded product comprising the resin composition. Effect of the Invention

[0016] The present invention can provide a resin composition that has both high fuel permeation resistance and weldability with a weldable material (polyolefin resin). In addition, the present invention can provide a resin molded product that is excellent in moldability and suppresses surface peeling by using the resin composition of the present invention. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing the shape and observation points of a test piece used in evaluation by microscopic infrared spectroscopy. [Diagram 2] FIG. 2 is a diagram showing the shape of a test piece used in evaluating weldability with a welding material. [Diagram 3] FIG. 2 is a diagram showing the shape of a test tool used for evaluating fuel permeation resistance. [Figure 4] FIG. 1 shows the shape of a test piece used in evaluating moldability and the observation points. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the following embodiments, and can be practiced with appropriate modifications within the scope of the object of the present invention.

[0019] The polyamide resin composition of the present invention is a resin composition in which the blending ratios of the polyolefin resin (a) and the polyamide resin (b) are 70 to 30% by weight and 30 to 70% by weight, respectively, relative to 100% by weight of the total of the polyolefin resin (a) and the polyamide resin (b), and when the surface of a resin molded article made of the resin composition is measured by microscopic infrared spectroscopy, the peak intensity ratio of the spectrum obtained based on the above formula (1) is 3.0 to 5.0.

[0020] Each component constituting the polyamide resin composition will be described below.

[0021] The (a) polyolefin resin used in the present invention is a thermoplastic resin obtained by polymerizing or copolymerizing olefins such as ethylene, propylene, butene, isoprene, and pentene. Specific examples include homopolymers such as polyethylene, polypropylene, polystyrene, polyacrylic acid esters, polymethacrylic acid esters, poly1-butene, poly1-pentene, and polymethylpentene, ethylene / α-olefin copolymers, vinyl alcohol ester homopolymers, polymers obtained by hydrolyzing at least a portion of vinyl alcohol ester homopolymers, [polymers obtained by hydrolyzing at least a portion of copolymers of (ethylene and / or propylene) and vinyl alcohol esters], [copolymers of (ethylene and / or propylene) and (unsaturated carboxylic acid and / or unsaturated carboxylic acid esters)], [copolymers of (ethylene and / or propylene) and (unsaturated carboxylic acid and / or unsaturated carboxylic acid esters) in which at least a portion of the carboxyl groups of the copolymers are metal salts], block copolymers of conjugated dienes and vinyl aromatic hydrocarbons, and hydrogenated products of the block copolymers.

[0022] Among these, polyethylene, polypropylene, ethylene / α-olefin copolymers, and copolymers of (ethylene and / or propylene) and (unsaturated carboxylic acid and / or unsaturated carboxylate) and copolymers of (ethylene and / or propylene) and (unsaturated carboxylic acid and / or unsaturated carboxylate ester) in which at least a portion of the carboxyl groups has been converted into a metal salt are preferred.

[0023] The ethylene / α-olefin copolymer referred to here is a copolymer of ethylene and at least one α-olefin having 3 to 20 carbon atoms. Specific examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, Examples of the α-olefins include 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and combinations thereof. Among these α-olefins, copolymers using α-olefins having 3 to 12 carbon atoms are preferred from the viewpoint of improving mechanical strength. The ethylene / α-olefin copolymer has an α-olefin content of preferably 1 to 30 mol%, more preferably 2 to 25 mol%, and even more preferably 3 to 20 mol%.

[0024] Furthermore, at least one of non-conjugated dienes such as 1,4-hexadiene, dicyclopentadiene, 2,5-norbornadiene, 5-ethylidenenorbornene, 5-ethyl-2,5-norbornadiene, and 5-(1'-propenyl)-2-norbornene may be copolymerized.

[0025] The unsaturated carboxylic acid used in the copolymer of (ethylene and / or propylene) and (unsaturated carboxylic acid and / or unsaturated carboxylic acid ester) is either acrylic acid or methacrylic acid, or a mixture thereof. Examples of such unsaturated carboxylic acid ester include methyl ester, ethyl ester, propyl ester, butyl ester, pentyl ester, hexyl ester, heptyl ester, octyl ester, nonyl ester, decyl ester, etc. of these unsaturated carboxylic acids, or mixtures thereof. In particular, a copolymer of ethylene and methacrylic acid, or a copolymer of ethylene, methacrylic acid, and an acrylic acid ester is preferred.

[0026] Among these (a) polyolefin resins, low, medium and high density polyethylene, polypropylene and ethylene / α-olefin copolymers are preferred. Low, medium and high density polyethylene are more preferred. From the viewpoint of durability, fuel permeation resistance, heat resistance and the like, and a density of 0.94 to 0.97 g / cm3 are particularly preferred. 3 It is a high density polyethylene.

[0027] The melt flow rate (hereinafter abbreviated as MFR: ASTM D1238) of the (a) polyolefin resin of the present invention is preferably 0.01 to 70 g / 10 min., and more preferably 0.01 to 60 g / 10 min. If the MFR is less than 0.01 g / 10 min., the fluidity is poor. On the other hand, if it exceeds 70 g / 10 min., the impact strength of the resin molded product may be reduced depending on the shape of the resin molded product.

[0028] The method for producing the polyolefin resin (a) used in the present invention is not particularly limited, and any method such as radical polymerization, coordination polymerization using a Ziegler-Natta catalyst, anionic polymerization, or coordination polymerization using a metallocene catalyst can be used.

[0029] In the present invention, it is preferable that the (a) polyolefin resin is partially or entirely modified with at least one compound selected from unsaturated carboxylic acids and / or derivatives thereof. The use of the modified (a) polyolefin resin improves compatibility and impact resistance. In addition, the resin molded product of the obtained resin composition is less likely to have surface peeling and tends to have excellent moldability.

[0030] The unsaturated carboxylic acids and / or derivatives thereof used as the modifier are as follows: acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, methylmaleic acid, methylfumaric acid, mesaconic acid, citraconic acid, glutaconic acid and metal salts of these carboxylic acids, methyl hydrogen maleate, methyl hydrogen itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, methyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, isocyanate, ethyl methacrylate ... Dimethyl octaconic acid, maleic anhydride, itaconic anhydride, citraconic anhydride, endobicyclo-(2,2,1)-5-heptene-2,3-dicarboxylic acid, endobicyclo-(2,2,1)-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, glycidyl acrylate, glycidyl methacrylate, glycidyl methacrylate, glycidyl itaconate, glycidyl citraconic acid, and 5-norbornene-2,3-dicarboxylic acid. Among these, unsaturated dicarboxylic acids and their acid anhydrides are preferred, and maleic acid and maleic anhydride are particularly preferred.

[0031] In the present invention, it is preferable to use, as the (a) polyolefin resin, a combination of (a-1) modified polyolefin resin and (a-2) unmodified polyolefin resin.

[0032] The amount of the unsaturated carboxylic acid or its derivative component introduced into the (a-1) modified polyolefin resin of the present invention is preferably in the range of 12 mgKOH / g to 35 mgKOH / g in terms of the acid value (JIS K 0070 (1992)) of the (a-1) modified polyolefin resin from the viewpoints of compatibility, molding processability, and weldability with the weld material. In this range, the compatibility with the (b) polyamide resin is improved. In particular, the phase structure of the resin molded product surface in the (a) polyolefin resin component and the (b) polyamide resin component is stabilized. In addition, the retention stability in the molten state during molding processing tends to be excellent, and thickening due to the influence of unreacted modifier is unlikely to occur. Furthermore, the (a) polyolefin resin component of the obtained resin composition contains a reactive functional group, thereby improving the weldability with the weld material. If it exceeds 35 mgKOH / g, the retention stability in the molten state during molding processing may be impaired, and thickening may easily occur. On the other hand, if it is less than 12 mgKOH / g, the weldability with the weld material may be impaired. A range of 14 mgKOH / g to 30 mgKOH / g is more preferable, and a range of 20 mgKOH / g to 25 mgKOH / g is even more preferable.

[0033] From the viewpoint of fuel permeation resistance, the blending ratio of the (a-2) unmodified polyolefin resin to the (a-1) modified polyolefin resin of the present invention is preferably 1 to 46% by weight and 99 to 54% by weight, respectively, based on the total of the (a-1) modified polyolefin resin and the (a-2) unmodified polyolefin resin being 100% by weight. More preferably, it is 10 to 44% by weight, 90 to 56% by weight, and even more preferably, it is 20 to 42% by weight and 80 to 58% by weight. In addition, within this blending ratio range, the phase structure of the (a) polyolefin resin component and the (b) polyamide resin component is stable. As a result, the composition of the present invention tends to have excellent retention stability in a molten state during molding and the like. In addition, a resin molded product with little discoloration such as yellowing of the composition can be obtained.

[0034] The (b) polyamide resin used in the present invention is a polyamide whose main components are amino acids, lactams, or diamines and dicarboxylic acids. Representative examples of the main components include amino acids such as 6-aminocaproic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, and para-aminomethylbenzoic acid, lactams such as ε-caprolactam and ω-laurolactam, tetramethylenediamine, hexamethylenediamine, 2-methylpentamethylenediamine, nonamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4- / 2,4,4-trimethylhexamethylenediamine, 5-methylnonamethylenediamine, metaxylylenediamine, paraxylylenediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, bis(4-aminocyclohexyl)cyclohexane, and the like. Examples of the diamines include aliphatic, alicyclic, and aromatic diamines such as bis(3-methyl-4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminopropyl)piperazine, and aminoethylpiperazine; and aliphatic, alicyclic, and aromatic dicarboxylic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 5-sodium sulfoisophthalic acid, 2,6-naphthalenedicarboxylic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid. In the present invention, nylon homopolymers or copolymers derived from these raw materials can be used alone or in the form of a mixture.

[0035] In the present invention, the polyamide resin (b) that is particularly useful is a polyamide resin that has a melting point of 150° C. or higher and is excellent in heat resistance and strength. Specific examples include polycaproamide (nylon 6), polyhexamethylene adipamide (nylon 66), polytetramethylene adipamide (nylon 46), polyhexamethylene sebacamide (nylon 610), polyhexamethylene dodecamide (nylon 612), polyundecane amide (nylon 11), polydodecanamide (nylon 12), polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), polycaproamide / polyhexamethylene terephthalamide copolymer (nylon 6 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (nylon 66 / 6T), polyhexamethylene adipamide / polyhexamethylene isopropyl alcohol, and the like. phthalamide copolymer (nylon 66 / 6I), polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (nylon 6T / 6I), polyhexamethylene terephthalamide / polydodecanamide copolymer (nylon 6T / 12), polyhexamethylene adipamide / polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (nylon 66 / 6T / 6I), polyxylylene adipamide (nylon XD6), polyhexamethylene terephthalamide / poly-2-methylpentamethylene terephthalamide copolymer (nylon 6T / M5T), polynonamethylene terephthalamide (nylon 9T) and mixtures thereof.

[0036] Among them, (b) polyamide resins are preferably nylon 6, nylon 66, nylon 610, nylon 6 / 66 copolymer, and copolymers having hexamethylterephthalamide units, such as nylon 6T / 66 copolymer, nylon 6T / 6I copolymer, nylon 6T / 12, and nylon 6T / 6 copolymer. Nylon 6 is particularly preferred. The use of nylon 6 is suitable for achieving both fuel permeation resistance and weldability with anti-weld materials. Furthermore, it is practically suitable to use these polyamide resins as a mixture depending on required properties such as impact resistance, moldability, and compatibility.

[0037] Although there is no particular limitation on the degree of polymerization of these (b) polyamide resins, the relative viscosity measured in a 98% concentrated sulfuric acid solution with a sample concentration of 0.01 g / ml at 25° C. is preferably in the range of 1.5 to 7.0. In particular, polyamide resins with a relative viscosity measured at 25° C. in the range of 2.0 to 6.0 are preferred.

[0038] In addition, the polyamide resin (b) of the present invention can preferably contain a copper compound to improve long-term heat resistance. Specific examples of the copper compound include cuprous chloride, cupric chloride, cuprous bromide, cuprous bromide, cuprous iodide, cupric iodide, cupric sulfate, cupric nitrate, copper phosphate, cuprous acetate, cupric acetate, cupric salicylate, cupric stearate, cupric benzoate, and complex compounds of the inorganic copper halides with xylylenediamine, 2-mercaptobenzimidazole, benzimidazole, and the like. Among them, monovalent copper compounds, particularly monovalent copper halide compounds, are preferred, and cuprous acetate and cuprous iodide are particularly preferred examples of the copper compound. The content of the copper compound is usually preferably 0.01 to 2 parts by weight, more preferably 0.015 to 1 part by weight, per 100 parts by weight of the polyamide resin (b). If the amount added is too large, metallic copper is liberated during melt molding, and the value of the product is reduced due to coloring. In the present invention, an alkali halide can be added in combination with the copper compound. Examples of the alkali halide compound include lithium chloride, lithium bromide, lithium iodide, potassium chloride, potassium bromide, potassium iodide, sodium bromide, and sodium iodide, with potassium iodide and sodium iodide being particularly preferred.

[0039] The preferred blending ratios of (a) polyolefin resin and (b) polyamide resin in the resin composition of the present invention are 30-70% by weight of (a) polyolefin resin and 70-30% by weight of (b) polyamide resin. More preferably, (a) polyolefin resin is 40-60% by weight and (b) polyamide resin is 60-40% by weight. If (a) polyolefin resin is less than 30% by weight, a phase structure having a specific higher-order structure cannot be obtained. As a result, in the present invention, the ratio of (a) polyolefin resin component present on the surface of the resin molded product decreases, and it becomes difficult to form a phase structure that satisfies the peak intensity ratio of the spectrum obtained based on the above formula (1). Then, it becomes difficult to achieve the object of the present invention. On the other hand, in the present invention, if (a) polyolefin resin exceeds 70% by weight, mechanical properties such as fuel permeation resistance, heat resistance and strength decrease.

[0040] The method for obtaining the resin composition of the present invention is not particularly limited, but may be, for example, a method in which (a) a polyolefin resin and (b) a polyamide resin are melt-kneaded in a twin-screw extruder.

[0041] In addition, other resins may be contained as long as the object of the present invention is not impaired.

[0042] The resin molded article made of the resin composition of the present invention may contain an inorganic filler in order to impart mechanical strength, rigidity, and fuel permeation resistance. The material is not particularly limited, but fibrous, plate-like, powdery, granular, and other fillers may be used. Specific examples of such fillers include fibrous fillers such as glass fiber, carbon fiber, potassium titanate whisker, zinc oxide whisker, alumina fiber, silicon carbide fiber, ceramic fiber, asbestos fiber, gypsum fiber, and metal fiber; silicates such as wollastonite, sericite, kaolin, mica, clay, bentonite, asbestos, talc, and alumina silicate; swellable layered silicates such as montmorillonite and synthetic mica; metal compounds such as alumina, silicon oxide, magnesium oxide, zirconium oxide, titanium oxide, and iron oxide; carbonates such as calcium carbonate, magnesium carbonate, and dolomite; sulfates such as calcium sulfate and barium sulfate; and non-fibrous fillers such as glass beads, ceramic beads, boron nitride, silicon carbide, calcium phosphate, and silica. These fillers may be hollow, and two or more of these fillers may be used in combination.

[0043] Furthermore, it is preferable to pre-treat these inorganic fillers with coupling agents such as isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds, and epoxy compounds, or with organic onium ions in the case of swellable layered silicates, in order to obtain better mechanical strength and resistance to fuel permeation.

[0044] The content of the inorganic filler is preferably 0.1 to 200 parts by weight per 100 parts by weight of the total amount of (a) polyolefin resin and (b) polyamide resin. The lower limit is more preferably 0.5 parts by weight or more, and particularly preferably 1 part by weight or more. On the other hand, the upper limit is preferably 200 parts by weight or less, and particularly preferably 150 parts by weight or less.

[0045] The composition of the present invention may contain other components within the range that does not impair the effects of the present invention, such as antioxidants and heat stabilizers (hindered phenols, hydroquinones, phosphites, and their substituted derivatives, etc.), weathering agents (resorcinols, salicylates, benzotriazoles, benzophenones, hindered amines, etc.), release agents and lubricants (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, various bisamides, bisureas, polyethylene wax, etc.), pigments (cadmium sulfide, phthalocyanine, carbon black, etc.), dyes (nigrosine, etc.), crystal nucleating agents (talc, silica, kaolin, clay, etc.), plasticizers, etc. Examples of the antistatic agent that can be added include antistatic agents (octyl p-oxybenzoate, N-butylbenzenesulfonamide, etc.), antistatic agents (anionic antistatic agents of alkyl sulfate type, cationic antistatic agents of quaternary ammonium salt type, nonionic antistatic agents such as polyoxyethylene sorbitan monostearate, betaine amphoteric antistatic agents, etc.), flame retardants (for example, hydroxides such as red phosphorus, melamine cyanurate, magnesium hydroxide, aluminum hydroxide, ammonium polyphosphate, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, brominated epoxy resin, or combinations of these brominated flame retardants with antimony trioxide, etc.), and other polymers.

[0046] The resin molded article made of the resin composition of the present invention is preferably a molded article having a phase structure in which (a) the polyolefin resin component is the continuous phase (matrix phase) and (b) the polyamide resin component is the continuous phase (matrix phase) in the thickness direction in part or in whole. This phase structure is observed by observing the cut surface of the molded article using a scanning electron microscope and a transmission electron microscope.

[0047] Furthermore, the effect of the present invention can be obtained by the presence of a large amount of (a) polyolefin resin component on the surface of a resin molded product made of the resin composition of the present invention. Here, the surface of the resin molded product refers to the surface that forms the outside of the molded product. Specifically, it refers to a range of 10 μm or less from the surface of the molded product in the thickness direction. By having a large amount of the polyolefin resin component in this range, the phase structure in the thickness direction of the resin molded product can be stably obtained. The proportion of the (a) polyolefin resin component present on the surface can be determined by microscopic infrared spectroscopy. Specifically, the distribution ratio of the (a) polyolefin resin component can be detected by performing a relative comparison of the absorbance of specific peaks of the (a) polyolefin resin and the (b) polyamide resin on the surface of the resin molded product. The detailed method is described below. The test piece shown in FIG. 1 (shape conforming to ISO19095-2 (2015) TyPeB) as a resin molded product is produced by injection molding (SE50DU manufactured by Sumitomo Heavy Industries, Ltd., cylinder temperature 260° C., mold temperature 80° C., injection speed 20 mm / s). Near the end of the flow shown in Figure 1 (a in Figure 1: 0.7 mm from the end of the flow of the molded product, 0.5 mm wide on the molded product), an infrared absorption spectrum (Fourier transform microscopic infrared spectroscopy) is measured by the attenuated total reflection method (ATR method) in a certain area (300 μm x 300 μm) on the surface of the resin molded product. The aperture size is 50 μm x 50 μm, and the resolution is 8 cm. -1 , 2950cm obtained by 100 times accumulation -1 Absorbance near 3300cm -1 Based on absorbance near 2950cm -1 The absorbance near 2850cm -1 ~3050cm -1 The value of the strongest absorbance peak was read within the range of 3300 cm. -1 The absorbance near 3200cm -1 ~3400cm -1The value is the peak with the strongest absorbance in the range. The average value of the peak intensity ratio calculated by the above formula (1) over a 300 μm square is 3.0 or more and 5.0 or less. By setting it in this range, the (a) polyolefin resin component is present in a large amount on the surface of the resin molded product, and entanglement due to molecular diffusion is likely to occur at the welding interface with the welding material, resulting in excellent welding properties. More preferably, the lower limit is 3.2 or more, and even more preferably, 3.5 or more. On the other hand, more preferably, the upper limit is 4.8 or less, and even more preferably, 4.5 or less. If it is less than 3.0, the (a) polyolefin resin component appearing on the surface of the resin molded product is small, so that the welding properties with the welding material are impaired. If it exceeds 5.0, the (a) polyolefin resin component appearing on the surface of the resin molded product is too much, so that the (a) polyolefin resin component on the surface absorbs and diffuses the fuel, resulting in impaired permeation resistance to the fuel. In addition, the relatively high elastic modulus (b) polyamide resin component is reduced on the surface, which causes the reinforcing effect of the welding interface with the welding material to be lost, impairing welding properties. Furthermore, the low crystallization temperature of (a) polyolefin resin component improves transferability during molding, causing the resin to stick to the mold, impairing mold release properties, and causing surface peeling on the resin molded product.

[0048] A resin molded article made of the resin composition of the present invention can be obtained, for example, by the following method.

[0049] The resin molded product made of the resin composition of the present invention is generally molded by melt molding, and in melt molding, a temperature difference or stress difference is likely to occur between the surface and the inside of the resin molded product during flow. Here, the inside of the resin molded product refers to a range of 45 to 55% from the surface of the resin molded product when the total thickness of the resin molded product is taken as 100%. In the present invention, this is actively utilized, and resins having different melt viscosity dependencies on shear rate are used as (a) polyolefin resin and (b) polyamide resin. Due to the difference in shear rate generated between the surface and the inside of the resin molded product, a matrix phase of the (a) polyolefin resin component can be formed on the surface of the resin molded product. When the higher of the melting points of (a) polyolefin resin and (b) polyamide resin is taken as Tp (°C), the melt viscosity ratio defined by the above formula (2) at Tp+20°C is 1216 s -1 In the above range, the upper limit is preferably 0.35 or more and 0.64 or less. More preferably, the lower limit is 0.40 or more, and even more preferably 0.45 or more. By setting the upper limit within this range, in a resin molded product using the present resin composition, the (a) polyolefin resin component having high weldability with the weld material (polyolefin resin) tends to be distributed on the surface, and the (b) polyamide resin component having high permeability resistance to fuel tends to be distributed inside. In addition, by setting the distribution in this manner, it may be possible to achieve both weldability with the weld material and permeability resistance to fuel. In addition, if the upper limit exceeds 0.64, molding defects such as surface peeling may occur in the resin molded product.

[0050] When multiple (a) polyolefin resins are used, the weight fraction of each (a) polyolefin resin relative to the total (a) polyolefin resin is multiplied by each melt viscosity and added together to determine the melt viscosity of the total (a) polyolefin resin. Specifically, the calculation method is as shown in the following formula (4).

[0051]

number

[0052] Here, MO is (a) the total blending ratio of polyolefin resin (wt%), MO iis the blending ratio (wt%) of each (a) polyolefin resin, VO i is the melt viscosity (Pa s) of each (a) polyolefin resin, and n is the number of (a) polyolefin resins used as raw materials.

[0053] When multiple (b) polyamide resins are used, the weight fraction of each (b) polyamide resin relative to the total (b) polyamide resin is multiplied by each melt viscosity and added together to determine the melt viscosity of the total (b) polyamide resin. Specifically, the calculation method is as shown in the following formula (5).

[0054]

number

[0055] Here, MA is the blending ratio (wt%) of the entire polyamide resin (b), MA i is the blending ratio (wt%) of each (b) polyamide resin, VA i is the melt viscosity (Pa s) of each (b) polyamide resin, and n is the number of (b) polyamide resins used as raw materials.

[0056] Measurement of the water absorption rate of a resin molded article made of the resin composition of the present invention is an index for controlling the phase structure of the resin molded article made of the resin composition of the present invention. If the water absorption rate of a resin molded article made of the resin composition of the present invention is high, it indicates that a large amount of the hydrophilic (b) polyamide resin component is present on the surface of the resin molded article, and if the water absorption rate is low, it indicates that a large amount of the hydrophobic (a) polyolefin resin component is present on the surface of the resin molded article.

[0057] The water absorption rate of the test piece made of the resin composition of the present invention is preferably 0.26% or more and 0.50% or less. If the water absorption rate is less than 0.26%, the fuel permeation resistance is impaired. From the viewpoint of further improving the fuel permeation resistance, the water absorption rate is more preferably 0.29% or more, and even more preferably 0.32% or more. On the other hand, if the water absorption rate exceeds 0.50%, the weldability with the welding material is impaired. From the viewpoint of further improving the weldability, the water absorption rate is preferably 0.46% or less, and even more preferably 0.42% or less. The specific method for measuring the water absorption rate is defined as the increase rate of the weight of the water-absorbed state based on the weight of the bone dry state when a test piece prepared by injection molding or the like is vacuum-dried (80°C, 14 hr, vacuum degree 1013 hPa) to be in an absolute dry state (absolute dry state) and immersed in water at 23°C for 24 hours. The test piece is a dumbbell-shaped test piece conforming to JIS K7139 (2009) Type A1, with dimensions of 170 mm in total length, 80 mm in parallel part length, 10 mm in width of parallel part, and 4 mm in thickness. The water absorption rate is calculated according to the above formula (3).

[0058] The flexural modulus of the molded article made of the polyolefin resin (a) of the present invention is preferably 0.5 to 1.3 GPa from the viewpoint of weldability with the weld material. The measurement method is calculated by a three-point bending test in accordance with ISO178 (2013). If the flexural modulus is less than 0.5 GPa, the rigidity of the resulting resin composition decreases, and the weldability with the weld material is impaired. If the flexural modulus is more than 1.3 GPa, stress concentration is likely to occur at the weld interface between the resin molded article made of the resin composition of the present invention and the weld material, and the weldability is impaired. In addition, when a plurality of polyolefin resins (a) are used, the weight fraction of each polyolefin resin (a) relative to the entire polyolefin resin (a) is multiplied by each flexural modulus and added together to obtain the flexural modulus of the entire molded article made of the polyolefin resin (a). Specifically, the calculation method of the following formula (6) is followed.

[0059]

number

[0060] Here, MO is (a) the total blending ratio of polyolefin resin (wt%), MO i is the blending ratio (wt%) of each (a) polyolefin resin, and X i is the flexural modulus (GPa) of the molded article made of each (a) polyolefin resin, and n is the number of (a) polyolefin resins used as raw materials.

[0061] The flexural modulus of the molded article made of the polyamide resin (b) of the present invention is preferably 2.5 to 3.0 GPa from the viewpoint of the weldability between the resin composition and the weld material. The measurement method is calculated by a three-point bending test in accordance with ISO178 (2013). If the flexural modulus is less than 2.5 GPa, the rigidity of the resulting resin composition is reduced, resulting in impaired weldability with the weld material. If the flexural modulus is more than 1.3 GPa, stress concentration is likely to occur at the weld interface between the resin molded article made of the resin composition of the present invention and the weld material, resulting in impaired weldability. In addition, when multiple polyamide resins (b) are used, the weight fraction of each polyamide resin (b) relative to the entire polyamide resin (b) is multiplied by each flexural modulus and added together to determine the overall flexural modulus of the molded article made of the polyamide resin (b). Specifically, the calculation method of the following formula (7) is followed.

[0062]

number

[0063] Here, MA is the blending ratio (wt%) of the entire polyamide resin, MA i is the blending ratio (wt%) of each (b) polyamide resin, Y i is the flexural modulus (GPa) of the molded product made of each (b) polyamide resin, and n is the number of (b) polyamide resins used as raw materials.

[0064] The resin molded article of the present invention may be shaped into various forms. In particular, known methods such as injection molding, extrusion molding, blow molding, and press molding can be used as a molding method for obtaining a melt-molded product. Among these, it is preferable to use injection molding, injection compression molding, and compression molding, since the object of the present invention can be easily achieved. The molding temperature is usually selected from a temperature range 5 to 50°C higher than the melting point of the (b) polyamide resin.

[0065] The structures obtained by various molding methods are generally single-layered, but may be multi-layered structures by methods such as two-color injection molding and co-extrusion molding. In the case of two-color injection molding and co-extrusion molding, the adhesion is excellent. Here, the multi-layer structure refers to a structure having the resin molded product of the present invention in at least one layer. There is no particular restriction on the arrangement of each layer, and all layers may be composed of the resin molded product of the present invention, or other layers may be composed of other thermoplastic resins.

[0066] Such a multilayer structure can be produced by a two-color injection molding method or the like. When the multilayer structure is to be obtained in the form of a film or sheet, the compositions forming each layer are melted in separate extruders and then fed into a die having a multilayer structure and then co-extrusion-molded, or the so-called laminate molding method in which the resin molded product layer of the present invention is melt-extruded after the other layers have been molded in advance. When the laminate structure has the shape of a hollow container such as a bottle, barrel, or tank, or a tubular body such as a pipe or tube, a normal co-extrusion molding method can be adopted. For example, in the case of a two-layer hollow molded product in which the inner layer is the resin molded product layer of the present invention and the outer layer is another resin layer, the resin molded product composition and the other resin composition are separately fed into two extruders, and these two molten resins are pressure-fed into a common die to form annular flows, and then the flows are joined so that the resin molded product layer is on the inner layer side and the other resin layer is on the outer layer side, and then the flows are co-extruded out of the die, and a two-layer hollow molded product can be obtained by a normal known tube molding method, blow molding method, or the like. In the case of a three-layered hollow molded article, it is possible to obtain a three-layered structure by the same method as above using three extruders, or to obtain a two-kind three-layered hollow molded article by using two extruders. Among these methods, it is preferable to use the co-extrusion molding method in terms of interlayer adhesive strength.

[0067] Examples of thermoplastic resins used for the other layers include saturated polyesters, polysulfones, polyethylene tetrafluoride, polyetherimides, polyamideimides, polyamide resins, polyketone copolymers, polyphenylene ethers, polyimides, polyethersulfones, polyetherketones, polythioetherketones, polyetheretherketones, thermoplastic polyurethanes, polyolefin resins, ABS, polyamide elastomers, and polyester elastomers. Mixtures of these resins or addition of various additives can also be used.

[0068] The resin molded article of the present invention can be preferably used as a gas and / or liquid transport or storage container and its accessory parts, taking advantage of its excellent permeation resistance, durability and moldability. Examples of gas and liquid include Flon-11, Flon-12, Flon-21, Flon-22, Flon-113, Flon-114, Flon-115, Flon-134a, Flon-32, Flon-123, Flon-124, Flon-125, Flon-143a, Flon-141b, Flon-142b, Flon-225, Flon-C318, R-502, 1,1,1-Trichloroethane, methyl chloride, methylene chloride, ethyl chloride, methyl chloroform, propane, isobutane, n-butane, dimethyl ether, castor oil-based brake fluid, glycol ether-based brake fluid, borate ester-based brake fluid, arctic brake fluid, silicone oil-based brake fluid, mineral oil-based brake fluid, power steering fluid, windshield washer fluid, gasoline, kerosene, diesel, heavy oil, toluene, isooctane, methanol, ethanol, isobutanol, butanol, nitrogen, oxygen, water Since the film has excellent permeability resistance to gases and / or liquids or vaporized gases such as nitrogen, carbon dioxide, methane, propane, natural gas, argon, helium, xenon, and pharmaceutical agents, it is widely used in a wide range of products, including, for example, permeability-resistant films for the above gases and / or liquids, airbags, bottles for various medicines such as shampoo, rinse, liquid soap, and detergent, tanks for storing medicines, tanks for storing gases, tanks for cooling liquids, tanks for transferring oil, tanks for disinfectants, tanks for blood transfusion pumps, fuel tanks, canisters, washer fluid tanks, oil reservoirs, and the like. Automotive parts such as oil tanks, medical equipment parts, tanks for general household appliances, bottle-shaped resin molded products, valves and joints such as cut-off valve covers and ORVR valve covers attached to these tanks and bottles, gauges for attached pumps, cases, fuel filler underpipes, ORVR hoses, reserve hoses, vent hoses, and other fuel tube connection parts (connectors, etc.), oil tube connection parts, brake hose connection parts, windshield washer fluid nozzles, connection parts for cooler hoses for cooling water and refrigerants, connection parts for air conditioner refrigerant tubes, connection parts for floor heating pipes, hoses for fire extinguishers and fire extinguishing equipment, connection parts and valves for tubes for medical cooling equipment, other applications for tubes for transporting chemical liquids and gases, applications requiring chemical liquids and permeation resistance such as containers for storing chemicals, automotive parts, internal combustion engines, machine parts such as housings for electric tools, electrical and electronic parts, medical, food, household and office supplies, building material-related parts, furniture parts, and other various applications. EXAMPLES

[0069] The present invention will be described in detail below with reference to examples.3 ~9 is a reference example 3 First, the evaluation methods used in the examples and comparative examples will be described.

[0070] (1) Water absorption A dumbbell-shaped test piece (JIS K7139 (2009) Type A1) with a total length of 170 mm, a parallel part length of 80 mm, a parallel part width of 10 mm, and a thickness of 4 mm was made by injection molding (NS60-9A manufactured by Nissei Plastic Industrial Co., Ltd., cylinder temperature 250°C, mold temperature 80°C, injection speed 24 mm / s, filling time 1.6 s). The test piece was vacuum dried (80°C, 14 hr, vacuum degree 1013 hPa) to an absolute dry state (absolutely dry state), and then immersed in water at 23°C for 24 hours, and then weighed. The water absorption rate was calculated according to the above formula (3).

[0071] The smaller the water absorption rate, the lower the water absorption.

[0072] (2) Fuel permeation resistance A square plate measuring 80 mm in length, 80 mm in width and 1 mm in thickness was molded by injection molding (NEX1000 manufactured by Nissei Plastic Industrial Co., Ltd., cylinder temperature 270°C, mold temperature 80°C, injection speed 60 mm / s), and cut into a disk shape with a diameter of 75 mm. Approximately 4.6 g of Fuel C (toluene / isooctane = 50 / 50 vol%) + E10 (ethanol 10 vol%) was placed in the aluminum cup shown in Figure 3, the disk-shaped test piece was set, the cup was sealed with a metal screw, and the test piece was annealed in an oven at 60°C so that the set test piece was facing upward. The weight change of the test piece was measured, and the fuel permeability (g / (m 2 The smaller the fuel permeability value, the better the resistance to fuel permeation.

[0073] (3) Weldability A rectangular test piece measuring 45 mm in length, 10 mm in width, and 1.5 mm in thickness was molded by injection molding (SE50DU manufactured by Sumitomo Heavy Industries, Ltd., cylinder temperature 260°C, mold temperature 80°C, injection speed 20 mm / s). Next, high-density polyethylene (MFR 5.8 g / 10 min at 190°C and a load of 2.16 kg, density 953 kg / m3 measured in accordance with ISO1183 (2013)) was injection welded to the rectangular test piece obtained by injection molding (SE50DU manufactured by Sumitomo Heavy Industries, Ltd., cylinder temperature 270°C, mold temperature 80°C, injection speed 20 mm / s, weld area approximately 5 x 10 -5 The test piece shown in Figure 2 was obtained by subjecting the obtained test piece (shape conforming to ISO19095-2 (2015) Type B) to a tensile test (Shimadzu Corporation Autograph AG-500C, tensile speed 5 mm / min) using a metal jig that fixed the obtained test piece (shape conforming to ISO19095-2 (2015) Type B) so that the interface between the primary material and the secondary material was parallel to the tensile direction. The maximum load (N) generated at that time was used to evaluate the weldability as the welding force.

[0074] (4) Molding processability A square plate (film gate) with a length of 60 mm, width of 60 mm, and thickness of 1 mm was molded by injection molding (NEX1000 manufactured by Nissei Plastic Industrial Co., Ltd., cylinder temperature 260°C, mold temperature 80°C, injection speed 140 mm / s), and this resin molded product was used as a test piece. A 40 mm square area near the gate of this test piece (a in Figure 4) was observed with a digital microscope (VHX-900 digital microscope manufactured by Keyence Corporation, magnification 5 times), and the entire observation area (40 mm square) was set as 100%, and the ratio of the area where surface peeling occurred to the entire observation area was used as an index of moldability, and was evaluated in the following items A to C. Surface peeling refers to a state in which a part of (a) the polyolefin resin component and / or (b) the polyamide resin component peels off from the surface of the molded product or blisters and turns white. The specific evaluation criteria were: (A) surface peeling of less than 1% of the entire observation surface; (B) surface peeling of 1% to less than 15% of the entire observation surface; and (C) surface peeling of 15% or more of the entire observation surface.

[0075] (5) Melt Viscosity Ratio Using a capillary rheometer (Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd.), the higher of the melting points of (a) polyolefin resin and (b) polyamide resin was defined as Tp (℃), and the shear rate at Tp + 20℃ was 1216 sec -1 The melt viscosity (Pa s) at each temperature was measured, and the melt viscosity ratio was calculated using the above formula (2).

[0076] (6) Acid value Measurements were performed based on JIS K 0070 (1992). (a-1) 1 g of modified polyolefin resin was precisely weighed and dissolved in 100 mL of xylene with stirring at approximately 120° C. After complete dissolution, a phenolphthalein solution was added, and neutralization titration was performed using a 0.1 mol / L ethanol solution of potassium hydroxide whose concentration had been determined in advance, to calculate the acid value.

[0077] (7) Flexural modulus In accordance with JIS K7139 (2009) Type A1, a dumbbell-shaped test piece (JIS The test specimens were vacuum dried (80°C, 14 hr, vacuum level 1013 hPa) to make them completely dry, and the flexural modulus of the molded products made of (a) polyolefin resin and (b) polyamide resin was measured using a three-point bending test method with a support distance of 64 mm in accordance with ISO178 (2013). For (a) polyolefin resin using multiple raw materials, the overall flexural modulus of the molded product made of (a) polyolefin resin was calculated from the flexural modulus of each molded product made of (a) polyolefin resin according to the above formula (6).

[0078] (8) Microscopic infrared spectroscopy The test piece shown in Figure 1 was produced by injection molding (SE50DU manufactured by Sumitomo Heavy Industries, Ltd., cylinder temperature 260°C, mold temperature 80°C, injection speed 20 mm / s). For the microinfrared spectroscopy analysis, the infrared absorption spectrum (Fourier transform microinfrared spectroscopy) was measured by total reflection measurement (ATR method) in a certain region (300 μm × 300 μm) shown in Figure 1 a (position 0.7 mm from the flow end of the molded product, 0.5 mm wide of the molded product). The peak intensity ratio was 2950 cm -1 Absorbance near 3300cm -1 The absorbance was calculated using the above formula (1) based on the absorbance in the vicinity of the sample. The analysis conditions were an aperture size of 50 μm × 50 μm, a resolution of 8 cm -1 The number of integration times was 100.

[0079] (9) (a-1) Modified polyolefin resin blend ratio The blending ratio of the (a-1) modified polyolefin resin was calculated according to the following formula (8), assuming that the total of the (a-2) unmodified polyolefin resin and the (a-1) modified polyolefin resin was 100% by weight.

[0080]

number

[0081] The raw materials used in each of the Examples and Comparative Examples are shown below. (a) The flexural modulus and acid value of the molded articles made of polyolefin resin are shown in the table.

[0082] (a-1) Modified polyolefin resin 1: MFR 5.0g / 10min at 190°C and a load of 2.16kg, density 954kg / m measured in accordance with ISO1183 (2013) 3 , a modified high-density polyethylene modified with maleic anhydride and having an acid value of 23.0 mg KOH / g.

[0083] (a-1) Modified polyolefin resin 2: MFR 5.8g / 10min at 190°C and a load of 2.16kg, density 954kg / m measured in accordance with ISO1183(2013) 3, a modified high-density polyethylene modified with maleic anhydride and having an acid value of 23.0 mg KOH / g.

[0084] (a-1) Modified polyolefin resin 3: MFR 1.7g / 10min at 190°C and a load of 2.16kg, density 960kg / m measured in accordance with ISO1183 (2013) 3 , a modified high-density polyethylene modified with maleic anhydride and having an acid value of 19.0 mg KOH / g.

[0085] (a-1) Modified polyolefin resin 4: MFR 5.0g / 10min at 190°C and a load of 2.16kg, density 954kg / m measured in accordance with ISO1183 (2013) 3 , a modified high-density polyethylene modified with maleic anhydride and having an acid value of 9.0 mg KOH / g.

[0086] (a-1) Modified polyolefin resin 5: MFR 5.8g / 10min at 190°C and a load of 2.16kg, density 952kg / m measured in accordance with ISO1183 (2013) 3 (a-2) Unmodified polyolefin resin 1: MFR 0.04g / 10min at 190℃ and a load of 2.16kg, density 953kg / m2 measured in accordance with ISO1183(2013) 3 High density polyethylene.

[0087] (a-2) Unmodified polyolefin resin 2: MFR 5.8g / 10min at 190°C and a load of 2.16kg, density 953kg / m measured in accordance with ISO1183(2013) 3 High density polyethylene.

[0088] (a-2) Unmodified polyolefin resin 3: MFR 0.03 g / 10 min at 190°C and a load of 2.16 kg, density 953 kg / m measured in accordance with ISO 1183 (2013) 3 High density polyethylene.

[0089] (a-2) Unmodified polyolefin resin 4: MFR 8.0g / 10min at 190°C and a load of 2.16kg, density 918kg / m measured in accordance with ISO1183(2013) 3 Low density polyethylene.

[0090] (b) Polyamide resin 1: Polyamide 6 with a melting point of 225°C and a relative viscosity of 2.35 measured using DSC. Approximately 10 mg of polyamide resin was sampled, and in a nitrogen atmosphere, a Perkin Elmer DSC (differential scanning calorimeter) was used to heat the polyamide resin from 40°C to 300°C at a heating rate of 20°C / min, hold it at 300°C for 1 minute, then lower it from 300°C to 40°C at a heating rate of 20°C / min, hold it at 40°C for 1 minute, and again raise it from 40°C to 300°C at a heating rate of 20°C / min. The temperature of the endothermic peak observed when this was done was taken as the melting point. A 98% concentrated sulfuric acid solution with a sample concentration of 0.01g / ml was prepared, and the relative viscosity was measured at 25°C using an Ostwald viscometer.

[0091] (b) Polyamide resin 2: Polyamide 610 with a melting point of 220°C and a relative viscosity of 2.7 measured using DSC. Approximately 10 mg of polyamide resin was sampled, and in a nitrogen atmosphere, a Perkin Elmer DSC (differential scanning calorimeter) was used to heat the polyamide resin from 40°C to 300°C at a heating rate of 20°C / min, hold it at 300°C for 1 minute, then lower it from 300°C to 40°C at a heating rate of 20°C / min, hold it at 40°C for 1 minute, and again raise it from 40°C to 300°C at a heating rate of 20°C / min. The temperature of the endothermic peak observed when this was done was taken as the melting point. A 98% concentrated sulfuric acid solution with a sample concentration of 0.01 g / ml was prepared, and the relative viscosity was measured at 25°C using an Ostwald viscometer.

[0092] (Examples 1 to 12, Comparative Examples 1 to 5) The above-mentioned (a-1) modified polyolefin resin, (a-2) unmodified polyolefin resin, and (b) polyamide resin were mixed in the blending ratios shown in Tables 2 and 3. Then, while removing volatile matter with a vacuum pump, the mixture was melt-extruded at a barrel set temperature of 230 to 250°C using a twin-screw extruder (Toshiba Machine Co., Ltd., TEM37) with a screw diameter of 37 mm. The discharge rate was 40 kg / hr, and the screw rotation speed was 350 rpm. The discharged resin was pulled into a strand shape, cooled by passing it through a cooling bath, and cut while being taken up with a pelletizer, to obtain pellets of the resin composition. The results of the above evaluations are shown in Tables 1, 2, and 3.

[0093] [Table 1]

[0094] [Table 2]

[0095] [Table 3]

[0096] From the results in Tables 1, 2, and 3, it can be seen that the resin composition of the present invention has both high fuel permeation resistance and weldability with the anti-weld material (polyolefin resin), and furthermore, the resin molded article has no surface peeling and is excellent in moldability. Therefore, it is a molded article that exhibits excellent properties even in a wide range of usage environments such as automotive applications. On the other hand, when the resin composition is outside the range of the present invention, it has both high fuel permeation resistance and weldability with the anti-weld material (polyolefin resin), and furthermore, surface peeling occurs in the resin molded article, and properties such as moldability are deteriorated. [Industrial Applicability]

[0097] The present invention provides a polyamide resin composition that is both highly resistant to fuel permeation and has excellent weldability with polyolefin resins. Furthermore, the polyamide resin composition does not cause surface peeling when molded into a resin product, and is particularly suitable for use in automobiles, medical devices, and general household appliances. [Explanation of symbols]

[0098] 1. Observation location 2. Molded products made from this resin composition 3. Molded products made of high density polyethylene 4. Molded products made from the resin composition 5. (Toluene / isooctane = 50 / 50 vol%) + E10 (ethanol 10 vol%) 6. Metal screws 7. Aluminum cup 8. Observation points 9. Gate 10. Test specimen

Claims

1. The resin composition has a blending ratio of the polyolefin resin (a) and the polyamide resin (b) of 70 to 30% by weight and 30 to 70% by weight, respectively, based on 100% by weight of the total of the polyolefin resin (a) and the polyamide resin (b), (a) the polyolefin resin comprises (a-1) a modified polyolefin resin and (a-2) an unmodified polyolefin resin, (a-1) the acid value of the modified polyolefin resin is 12 mgKOH / g to 35 mgKOH / g; (a) the flexural modulus of the molded article made of polyolefin resin is 0.5 to 1.3 GPa; (b) the flexural modulus of the molded article made of polyamide resin is 2.5 to 3.0 GPa; When the surface of a resin molded article made of the resin composition is measured by microscopic infrared spectroscopy, the peak intensity ratio of the spectrum obtained based on the following formula (1) is 3.0 to 5.0, When the higher of the melting points of (a) polyolefin resin and (b) polyamide resin is defined as Tp (°C), the melt viscosity ratio at Tp + 20°C defined by the following formula (2) is -1 0.35 to 0.64 in A dumbbell-shaped test piece is prepared in accordance with JIS K7139 (2009) Type A1, the total length being 170 mm, the length of the parallel portion being 80 mm, the width of the parallel portion being 10 mm, and the thickness being 4 mm. The test piece is immersed in water at 23°C for 24 hours, and a weight change is measured. The water absorption of the resin composition is calculated by the following formula (3) to be 0.26% to 0.50%. [0010] [0025] [0030]

2. 2. The resin composition according to claim 1, wherein the (a) polyolefin resin comprises a polyolefin resin modified with at least one compound selected from unsaturated carboxylic acids and derivatives thereof.

3. The resin composition according to claim 1 or 2, wherein the blending ratio of the modified polyolefin resin (a-1) and the unmodified polyolefin resin (a-2) is 1 to 46% by weight and 99 to 54% by weight, respectively, based on the total weight of the modified polyolefin resin (a-1) and the unmodified polyolefin resin (a-2).

4. A resin molded product comprising the resin composition according to any one of claims 1 to 3.

5. 5. The resin molded article according to claim 4, which is a container for transporting or storing gas and / or liquid or an accessory thereto.

Citation Information

Patent Citations

  • Electrically insulating composition and sheet molding

    JP2005085489A

  • Thermoplastic elastomer composition

    JP2014205781A

  • Resin composition and resin molding

    JP2018053090A

  • Resin molded article and its manufacturing method

    JP4032656B2

  • Porous sintered sheet and production method therefor

    WO2018207772A1